2009
DOI: 10.1002/cvde.200906795
|View full text |Cite
|
Sign up to set email alerts
|

Etching of Nb2O5 Thin Films by NbCl5

Abstract: Atomic layer deposition (ALD) of Nb 2 O 5 from NbCl 5 has earlier been found to produce highly non-uniform films. This was suspected to be due to etching of Nb 2 O 5 by NbCl 5 . In this work the effect of NbCl 5 vapor on Nb 2 O 5 thin films is studied with a quadrupole mass spectrometer (QMS) and a quartz crystal microbalance (QCM) in-situ in an ALD reactor. Nb 2 O 5 is deposited from Nb(OEt) 5 and water in the same reactor. NbCl 5 is found to etch the Nb 2 O 5 film producing volatile NbOCl 3 . The results are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(10 citation statements)
references
References 33 publications
0
10
0
Order By: Relevance
“…The initial process developed in this work, was the area-selective MoCl4O + (O3 + H2O) process. This was the first reported area-selective process for MoOx and usage of MoCl4O as an ALD-precursor, and moreover one of only a few reported oxychlorides used to deposit oxides [239,240]. Bergum et al had previously described usage of WCl4O in combination with H2O to deposit WO3, but the process seemed to stop after a few cycles according to their QCM data [238].…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…The initial process developed in this work, was the area-selective MoCl4O + (O3 + H2O) process. This was the first reported area-selective process for MoOx and usage of MoCl4O as an ALD-precursor, and moreover one of only a few reported oxychlorides used to deposit oxides [239,240]. Bergum et al had previously described usage of WCl4O in combination with H2O to deposit WO3, but the process seemed to stop after a few cycles according to their QCM data [238].…”
Section: Discussionmentioning
confidence: 96%
“…This may be due to the same substrate selectivity as seen for MoCl4O, and its growth should hence be revisited. In-situ generated NbOCl3 [239] and TaOCl3 [240] have been suggested as precursors for deposition of their binary oxides in combination with H2O. These oxychlorides have however, not been used directly.…”
Section: Mocl4o As An Ald-precursormentioning
confidence: 99%
“…The application of WCl 6 + H 2 O as a precursor combination was not considered practical due to likely formation of volatile WOCl 4 , in a similar manner to that reported for the application of NbCl 5 with H 2 O. 21 In the same work by Knapas et al, however, they showed that NbOCl 3 can be applied to the formation of lms of Nb 2 O 5 . Previous work on deposition of WO 3 lms by WF 6 (ref.…”
Section: Wo 3 Depositionmentioning
confidence: 88%
“…Nb 2 O 5 is a high-permittivity material with potential thin film applications in for instance DRAM devices (dynamic random access memory), optics, and gas sensors . Original growth experiments to deposit Nb 2 O 5 using the NbCl 5 −H 2 O ALD process failed due to etching of Nb 2 O 5 by NbCl 5 .…”
Section: Introductionmentioning
confidence: 99%
“…Original growth experiments to deposit Nb 2 O 5 using the NbCl 5 −H 2 O ALD process failed due to etching of Nb 2 O 5 by NbCl 5 . Recently we demonstrated that NbCl 5 and H 2 O may still be applicable for depositing Nb 2 O 5 by ALD if some Nb 2 O 5 is allowed to react with NbCl 5 before the substrates . In this approach the niobium containing species giving rise to growth of Nb 2 O 5 is NbOCl 3 .…”
Section: Introductionmentioning
confidence: 99%